The Relationships between ‘The San Diego Quick Reading Assessment’ and Students’ Perception on Second Language Reading Ability - Latiff Azmi, Mohd Nazri (2013)
Reading is a key for success in any learning process. This exploratory study was carried out in order to investigate student’s ability in second language reading by using a special assessment called the San Diego Quick Reading Assessment. The assessment was used to measure student’s ability in uttering and understanding the meaning of the words. At the same time, the objective of the research is also to investigate student’s perception on their reading ability. Therefore, the correlation or relationships of both instruments were used to get the findings. Overall findings show that the students did not score good grades in the assessment and similarly, they perceived that they did not have second language reading ability. The findings are important to be relied on for the future reading intervention programs to teachers, parents and educational bodies.